2022
DOI: 10.3389/fphar.2022.957771
|View full text |Cite
|
Sign up to set email alerts
|

Exosome derived from stem cell: A promising therapeutics for wound healing

Abstract: A wound occurs when the epidermis and dermis of the skin are damaged internally and externally. The traditional wound healing method is unsatisfactory, which will prolong the treatment time and increase the treatment cost, which brings economic and psychological burdens to patients. Therefore, there is an urgent need for a new method to accelerate wound healing. As a cell-free therapy, exosome derived from stem cell (EdSC) offers new possibilities for wound healing. EdSC is the smallest extracellular vesicle s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 158 publications
0
10
0
1
Order By: Relevance
“…Studies have shown that exosomes can inhibit the expression of proinflammatory factors, such as interleukin 1β (IL-1β), interleukin 6 (IL-6), Interferon γ (IFN-γ), and tumor necrosis factor α (TNF-α), and promote the expression of anti-inflammatory factors, such as transforming growth factor β (TGF-β), interleukin 4 (IL-4), and interleukin 10 (IL-10), thereby inhibiting inflammation and accelerating healing. Exosomes can also inhibit inflammation and promote healing by promoting macrophage M2 polarization and inhibiting the function of T cells. , In addition, there are many other cell types involved in wound healing, including keratinocytes, fibroblasts. An important limitation of this study is the singular focus on HUVECs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have shown that exosomes can inhibit the expression of proinflammatory factors, such as interleukin 1β (IL-1β), interleukin 6 (IL-6), Interferon γ (IFN-γ), and tumor necrosis factor α (TNF-α), and promote the expression of anti-inflammatory factors, such as transforming growth factor β (TGF-β), interleukin 4 (IL-4), and interleukin 10 (IL-10), thereby inhibiting inflammation and accelerating healing. Exosomes can also inhibit inflammation and promote healing by promoting macrophage M2 polarization and inhibiting the function of T cells. , In addition, there are many other cell types involved in wound healing, including keratinocytes, fibroblasts. An important limitation of this study is the singular focus on HUVECs.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that exosomes can promote wound healing by promoting the proliferation and migration of keratinocytes, enhancing re-epithelialization. Exosomes can also regulate ECM remodeling by promoting the function of fibroblasts, inhibiting the differentiation of fibroblasts into myofibroblasts, and regulating the proportion of collagen, so as to promote wound healing better . Therefore, the specific mechanisms by which hADSCs-Exo, miR-148a-3p, and PF-127 hydrogel act on other responses and other cell types in skin lesion recovery require elucidation through further research.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exosome-based cancer therapy is the beginning of a next generation of cancer treatment . Although exosome-based cancer therapeutic approaches show promising results, there are some questions that have not been solved such as exosome heterogeneity, large-scale production, diversity of beach production (individual batches get different exosomes), and therapeutic exosome toxicological investigation. Stem cell-derived exosome is a potential source of therapeutic exosomes . Research evidence indicates that stem cell exosomes also promote cancer; if stem cell-derived exosomes are not modified, they can promote cancer or inhibit it .…”
Section: Exosome-based Therapeutic Approach For the Emtmentioning
confidence: 99%
“…Conclusively, the exosomes released after trauma or surgery appear to play a significant role in healing. Although the exact mechanism is still unclear, current research aims to identify exosomes as promising targets for future therapeutic interventions [ 169 ].…”
Section: Relationship Between Exosomes Biogenesis and Actions With Dr...mentioning
confidence: 99%